ARSIP DIGITAL UNTUK EFISIENSI PENGELOLAAN DAN PERCEPATAN PELAYANAN - Pranata, Muhammad Refki (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2024)
In this research, the author wants to convey that archive digitization is very useful in accelerating management in a service agency. The purpose of this writing is to tell how important digitization is today. The research method used by the author is qualitative with the literature study method. With the digitization of this archive, it will be easier to be able to overcome all obstacles related to the preservation of the physical form of the archive, efficiency for storage, archive movement and archive retrieval. With this form of digital archive, all matters relating to institutions, organizations and agencies will become easier. the conclusion obtained is that digital archives are needed now to help speed up services in an agency, because it will make it easier for an agency to retrieve information.